Characterising the impacts of emerging energy development on wildlife, with an eye towards mitigation - Northrup, Joseph M., author; Wittemyer, George, author; Blackwell Publishing Ltd., publisher (Colorado State University. Libraries, 2012)
Global demand for energy is projected to increase by 40% in the next 20 years, and largely will be met with alternative and unconventional sources. Development of these resources causes novel disturbances that strongly impact terrestrial ecosystems and wildlife. To effectively position ecologists to address this prevalent conservation challenge, we reviewed the literature on the ecological ramifications of this dominant driver of global land-use change, consolidated results for its mitigation and highlighted knowledge gaps. Impacts varied widely, underscoring the importance of area and species-specific studies. The most commonly reported impacts included behavioural responses and direct mortality. Examinations of mitigation were limited, but common easements included (1) reduction of the development footprint and human activity, (2) maintenance of undeveloped, 'refuge' habitat and (3) alteration of activity during sensitive periods. Problematically, the literature was primarily retrospective, focused on few species, countries, and ecoregions, and fraught with generalisations from weak inference. We advocate future studies take a comprehensive approach incorporating a mechanistic understanding of the interplay between development caused impacts and species ecology that will enable effective mitigation. Key areas for future research vital to securing a sustainable energy future in the face of development-related global change are outlined.
Characterizing the impacts of emerging energy development on wildlife, with an eye towards mitigation
Keywords: wilderness; best management practices; conservation; energy extraction; industrial development; land conversion; renewable energy; alternative energy